DISCECTOMY BY HEMILAMINECTOMY FOR LUMBAR DISC SYNDROME - DR. NARASIMHA RAO,; DR. AMAR VISHAL, (International Journal of Pharma and Bio Sciences, 2014)
Our objective is to study and evaluate the clinical outcome of surgical treatment of lumbar disc prolapse by hemilaminectomy and discectomy technique. 32 patients were operated in ASRAM medical college and hospital , eluru. All patients were available for follow up by visits or questionnaire by letters. Mean follow up of 32 patients was 9 months with a minimum of 3 months and maximum of 24 months. Patients with clinically and radiologically diagnosed lumbar disc prolapse with following indications like disc prolapse with bowel and bladder symptoms(cauda equina syndrome), disc prolapse with severe sensory or motor deficits, disc prolapse with progressive neurological deficits, disc prolapse with sciatica(unilateral or bilateral sciatica) which is decreased by conservative measures (rest ,anti-inflammatory medication or even epidural steroid) but returned to initial level after a minimum of 6-8 weeks of above mentioned conservative methods and age group of 20-60 years. Exclusion criteria includes lumbar disc prolapse other than L4-L5and L5-S1, far lateral disc prolapses compressing the nerve in the forearm as proved by CT scan or MRI, recurrent disc herniations and presence of other associated spinal pathology Out of 32 patients at the time of discharge, 28 patients (87.5%) could walk independently without any aid and without any radicular pain. 4 patients with little radicular pain and with support. In most of the patients 28 (87.5%) sciatica improved immediately. Hemilaminectomy and discectomy is a safe and reliable method treating patients with lumbar disc prolapse who have been closely scrutinized for surgery.